Inteligencia Emocional y Satisfacción Laboral del Personal de la Administración Municipal de Montenegro - Quindío. (2021)
The present quantitative research work aimed to correlate two variables in the field of organizational psychology, such as: emotional intelligence and job satisfaction. It counted with the collaboration of 21 officials of the municipal administration (mayoralty) of the municipality of Montenegro-Quindío. In order to determine the level of emotional intelligence, the EQ i inventory of BarOn (1980) was approached and to measure the level of job satisfaction, the SL SPC (1999) job satisfaction scale of Palma was applied. This made it possible to determine and establish as the main results, an emotional coefficient at an average level, showing that the staff manages to self-regulate, motivate themselves and recognize their own emotions and those of others. However, a low capacity for empathy with their coworkers and bosses was perceived. Regarding job satisfaction, it was found at a regular level. Regarding the correlation of the two variables, it was possible to identify that there is a moderate correlation, standing out significantly among the indicators of the personal development factor, with the dimensions of the interpersonal, intrapersonal and general mood components. As well as the task performance factor with the dimensions of the intrapersonal components and general mood. Keywords: personal development, task performance, emotional intelligence, intr